Bangladesh : Report on the Observance of Standards and Codes; Fiscal Transparency Module; Update. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This paper presents an update to the Report on the Observance of Standards and Codes (ROSC) on Fiscal Transparency for Bangladesh. The paper discusses that the authorities have implemented a number of measures recommended in the ROSC, particularly those aimed at establishing reliable fiscal reports, and have moved toward establishing an effective basis for medium-term budgeting. Progress on longer-term issues with regard to improving reporting and control over quasi-fiscal activities of state-owned enterprises and strengthening government watchdog institutions will require continuing sustained effort.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet